Improving long-term storage and cryopreservation of boar sperm using antioxidants (GameteGuard®) with novel experimental approaches - Shepherd, Myles Jon, author; Barfield, Jennifer, advisor; Bouma, Gerrit, advisor; Schwab, Clint, committee member; Herickhoff, Lisa, committee member; Weller, Zach, committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.
Keywords: cryopreservation; Plackett-Burman; sperm; flow cytometry; boar; semen